Compulsive online shopping in Malaysia / Chuah Soo Cheng, Ng Phaik Lian and Noor Rita Mohamad Khan - Cheng Chuah, Soo; Lian Ng, Phaik; Mohamad Khan, Noor Rita (UiTM Press, 2018)
The proliferation of e-commerce has induced the online shopping transactions around the world. The increase trend of online shopping illustrates that there is a dramatic increase in compulsive behavior on online shopping. Shopping online could give an illusion to the consumers that they are not really spending money and become compulsive for many consumers. By adapting the questionnaires outlined, this study validates the compulsive online shopping scale to measure the compulsive online shopping behaviour in Malaysia context. A survey was conducted with a sample of 221 respondents based on convenience-sampling method in the Klang Valley. The factor analysis showed high reliable test of Cronbach alpha for the scales underlying the compulsive online shopping behavior.